Визначення поперечного переміщення робочих органів широкозахватних агрегатів - Ігнатьєв, Євген Ігорович; Игнатьев, Евгений Игоревич; Ihnatiev, Yevhen; Босенко, І. С. (ТДАТУ, 2016)
The transverse movement of the working bodies of 18-row wide working unit with the tractor HTZ-160 depending on the angle of rotation of the tractor and placing them in the aggregate are considered. Recommended kinematic parameters and circuit of coupling.
Keywords: unit; tractor; hitch; working bodies; placement; angle; deviation; scheme